(untitled) (TAMADDUN NURI JURNALI, 2024)
In today’s era of globalization, the issue of the spiritual environment of society exerting its influence on other spheres of society’s life is becoming increasingly relevant. Especially since this environment plays an important role in the education of young people, the management of society should strengthen the legal foundations of the socio-spiritual environment. Because many factors come to the surface that lead to a weakening of the social and spiritual environment.